Goose STING mediates IFN signaling activation against RNA viruses - Fu, Feiyu; Lin, Zhenyu; Li, Yanlin; Wang, Jie; Li, Yawen; Liu, Pengcheng; Wang, Zhaofei; Ma, Jingjiao; Yan, Yaxian; Sun, Jianhe; Cheng, Yuqiang (Frontiers in Immunology, 2022)
Stimulator of the interferon gene (STING) is involved in mammalian antiviral innate immunity as an interferon (IFN) activator. However, there is still a lack of clarity regarding the molecular characterization of goose STING (GoSTING) and its role in the innate immune response. In the present study, we cloned GoSTING and performed a series of bioinformatics analyses. GoSTING was grouped into avian clades and showed the highest sequence similarity to duck STING. The in vitro experiments showed that the mRNA levels of GoSTING, IFNs, IFN-stimulated genes (ISGs), and proinflammatory cytokines were significantly upregulated in goose embryo fibroblast cells (GEFs) infected with Newcastle disease virus (NDV). Overexpression of GoSTING in DF-1 cells and GEFs strongly activated the IFN-β promoter as detected by a dual-luciferase reporter assay. Furthermore, overexpression of GoSTING induced the expression of other types of IFN, ISGs, and proinflammatory cytokines and inhibited green fluorescent protein (GFP)-tagged NDV (NDV-GFP) and GFP-tagged vesicular stomatitis virus (VSV) (VSV-GFP) replication in vitro. In conclusion, these data suggest that GoSTING is an important regulator of the type I IFN pathway and is critical in geese's innate immune host defense against RNA viruses.